2020
DOI: 10.5530/bems.6.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Natural Compounds from Tinospora cordifolia Against SARS-CoV-2 Protease, Surface Glycoprotein and RNA Polymerase

Abstract: Background: Antiviral activity of natural compounds from Tinospora cordifolia (Amritaballi) were evaluated for their efficacy against SARS-CoV-2 targets involved in virus attachment and replication. Materials and Methods: The binding efficacy (binding affinity, K i and IC 50 values) of natural compounds from Tinospora cordifolia were tested using in silco tools against four key SARS-CoV-2 targets i.e., 1) surface glycoprotein (6VSB) and 2) Receptor binding domain (6M0J) both responsible for attachment of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 19 publications
3
42
0
Order By: Relevance
“…Likewise, an in-silico study by Tripathi et al 40 determined that Withanoside IV and V can bind to M Pro . Sagar and Kumar 41 noted that Magnoflorine and Palmatine bind to SARS-CoV-2 M Pro , surface glycoprotein and RNA polymerase. Chowdhury et al 42 predicted that tetrahydropalmatine, an important phytoconstituent of T. cordifolia , can bind SARS-CoV-2 M pro , although, this phytocompound was not detected in Coronil by UHPLC analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, an in-silico study by Tripathi et al 40 determined that Withanoside IV and V can bind to M Pro . Sagar and Kumar 41 noted that Magnoflorine and Palmatine bind to SARS-CoV-2 M Pro , surface glycoprotein and RNA polymerase. Chowdhury et al 42 predicted that tetrahydropalmatine, an important phytoconstituent of T. cordifolia , can bind SARS-CoV-2 M pro , although, this phytocompound was not detected in Coronil by UHPLC analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 49 A study by Yan et al 50 found that rosmarinic acid can also bind to SARS-CoV-2 M Pro . Tinocordiside, a major phytochemical present in T. cordifolia has been reported by multiple independent computational studies to interact with SARS-CoV-2 surface glycoprotein and RNA polymerase, 41 besides the viral MPro. 39 , 41 In-silico study from our group also showed that tinocordiside binds at the interface of ACE-2-RBD complex and energetically weakens this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…rcsb.org/) and were optimized for molecular docking in the Chimera software as reported before. [13][14][15][16][17] Molecular docking was performed to evaluate the binding affinity of two compounds (Methyl Eugenol and Ursolic Acid) reported in Ocimum extract against the olfactory receptors using AutoDock Vina and the docked proteinligand complex were visualised using the Chimera and PyMOL v 1.8.2.0 software as reported before. [13][14][15][16][17]…”
Section: Methodsmentioning
confidence: 99%
“…However, they did not study all the parameters but hypothesized that Tinospora cordifolia extract could be used as an adjunct to HIV management. The in silico approach against SARS-CoV-2 was tested by Sagar and Kumar [ 61 ]. The key targets they considered for the docking were surface glycoprotein, receptor-binding domain, RNA-dependent RNA polymerase, and protease.…”
Section: Plants As a Source Of Medicine Against Sars-cov-2mentioning
confidence: 99%
“…The key targets they considered for the docking were surface glycoprotein, receptor-binding domain, RNA-dependent RNA polymerase, and protease. The natural compounds from Tinospora cordifolia such as berberine, isocolumbin, magnoflorine, and tinocordiside showed high binding efficacy against all four key targets [ 61 ].…”
Section: Plants As a Source Of Medicine Against Sars-cov-2mentioning
confidence: 99%